2013
DOI: 10.1128/aem.03107-12
|View full text |Cite
|
Sign up to set email alerts
|

Surveying the Microbiome of Ants: Comparing 454 Pyrosequencing with Traditional Methods To Uncover Bacterial Diversity

Abstract: We are only beginning to understand the depth and breadth of microbial associations across the eukaryotic tree of life. Reliably assessing bacterial diversity is a key challenge, and next-generation sequencing approaches are facilitating this endeavor. In this study, we used 16S rRNA amplicon pyrosequencing to survey microbial diversity in ants. We compared 454 libraries with Sanger-sequenced clone libraries as well as cultivation of live bacteria. Pyrosequencing yielded 95,656 bacterial 16S rRNA reads from 19… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

6
96
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 112 publications
(103 citation statements)
references
References 59 publications
6
96
1
Order By: Relevance
“…By using PCR amplification and DNA sequencing techniques, previous studies have shown that members of the 'Verrucomicrobia' constitute part of a stable, autochthonous community of symbionts maintained in the guts of Cephalotes 'turtle' ants (Anderson et al, 2012;Kautz et al, 2013;Russell et al, 2009). These symbionts are protected by a proventricular filter (Lanan et al, 2016), remain stable in laboratory-reared colonies and likely coevolved with their hosts (Sanders et al, 2014).…”
mentioning
confidence: 99%
“…By using PCR amplification and DNA sequencing techniques, previous studies have shown that members of the 'Verrucomicrobia' constitute part of a stable, autochthonous community of symbionts maintained in the guts of Cephalotes 'turtle' ants (Anderson et al, 2012;Kautz et al, 2013;Russell et al, 2009). These symbionts are protected by a proventricular filter (Lanan et al, 2016), remain stable in laboratory-reared colonies and likely coevolved with their hosts (Sanders et al, 2014).…”
mentioning
confidence: 99%
“…Heteropteran stinkbugs have developed highly species-specific associations with individual gut symbionts that are either maternally transmitted or acquired early in development (44)(45)(46). Other insects have established stable relationships with simple gut communities, including honey and bumble bees (47,48) and ants (49). While the mechanisms by which bees regulate their gut microbiome have not been established, the Sonoran Desert turtle ant, Cephalotes rohweri, was recently found to have a mechanical filter that blocks any bacteria or particles larger than 0.2 m from entering into the midgut and hindgut after an initial gut microbiome is established (50).…”
Section: Discussionmentioning
confidence: 99%
“…Massively parallel next-generation sequencing technologies have allowed significant leaps forward in the power with which we may sample microbial communities. These methods do not have the constraint of having to culture species to analyse them, but instead evaluate DNA directly isolated from the substrate of interest (Su et al, 2012;Kautz et al, 2013;Bokulich et al, 2014;Taylor et al, 2014). So far, studies utilising these techniques are providing increasing evidence that many microbial communities are not homogenised through space, but display significant structure just like many plant and animal communities do (Martiny et al, 2006;Hanson et al, 2012;Nemergut et al, 2013).…”
Section: Introductionmentioning
confidence: 99%